TRADISI YASINAN BAGI MASYARAKAT NAGARI TANJUNG KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Muslim Muslim; Rahmi Rahmi; Lisma Fitriani (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The background of writing this thesis is because the author sees the phenomenon of living the Al-Qur’an which is a tradition in the people of Nagari Tanjung, by privileging the surah Yasin. Whereas the Al-Qur’an which was revealed 114 surahs, if traced its meaning and content will be obtained its own advantages and privileges. This is seen as “subordinating” other suras in the Qur’an. The author examines several things related to the origins of the yasinan tradition, the characteristics and practices of the yasinan tradition, and the meaning of the yasinan tradition for the people of Nagari Tanjung. This research is a field research with data collection techniques through observation and interviews with informans using purposive sampling and documentation techniques. Furthermore, the data found in the field were classified and then analyzed using descriptive qualitative analysis method. The result of the of the study show that first, the yasinan tradition has existed for about 20 years, was born due to the lack of mother’s role in the tahlilan tradition. Second, the characteristics of the yasinan tradition in Nagari Tanjung include: the yasinan group is divided into two: each Jorong and the mosque congregation yasinan group, wearing uniform or side cloths, with the time of the yasinan being divided into two: as a weekly agenda and when death occurs. Third, the practice of the yasinan tradition in Nagari Tanjung is a form of living Qur’an by reciting surah Yasin together accompanied by special prayer, then closed with a meal together and gathering for woman’s group. Fourth, the meaning of the community towards the yasinan tradition in Nagari Tanjung include: because surah Yasin is seen as the heart of Al-Qur’an, reading is like reading the Qur’an ten times (khatam Qur’an), being a prayer for death people, can strengthen the relationship between each other. Then the yasinan tradition is considered as a place to bring the Qur’an to life in the midst of modern life.